2021
DOI: 10.22271/oral.2021.v7.i1e.1150
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and color stability of 3D printed temporary crown material in different oral media (In vitro study)

Abstract: To evaluate the effect of different oral media (artificial saliva, carbonated orange juice and coffee) on the surface roughness and color stability of 3D printed temporary material. Methodology: twenty one discs samples were designed using additive manufacturing technique (SLA) were divided into 3 groups and stored in artificial saliva, coffee and carbonated orange juice at 37 ℃. Surface roughness was measured before and after immersion using non-contact USB Digital microscope. Color measurements were made bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In the current study the storage time significantly affected color change (ΔE) which increased, so time plays a role in the staining of provisional resin materials. This may be due to precipitation of stains over time which agreed with Radwan et al [41] and Bastos et al [42] . Where the ΔE increased progressively over time, regardless of material and media that may be due to increased water sorption over time.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study the storage time significantly affected color change (ΔE) which increased, so time plays a role in the staining of provisional resin materials. This may be due to precipitation of stains over time which agreed with Radwan et al [41] and Bastos et al [42] . Where the ΔE increased progressively over time, regardless of material and media that may be due to increased water sorption over time.…”
Section: Discussionsupporting
confidence: 82%
“…The outcomes attributed to water sorption causes water to penetrate into the matrix of a 3D printing polymer structure (26) . This results was agreed with Radwan (2021) (27) ; Gad et al (2022) (28) . Acidic pH and beverage pigments such as coffee, tea, lemon juice, orange juice, red wine, and coke-based drinks have been shown to have a negative impact on acrylic resin dentures, resulting in increased surface roughness (29) .…”
Section: D Printing Denture Basesupporting
confidence: 91%
“…Radwan et al 20 produced disc samples with SLA printer technologies and concluded that coffee has the most staining effect on the examined 3D‐printed materials. Çakmak et al 21 conducted a study to compare the effect of tooth brushing and thermal cycling on the colour stability of 3D printing denture base resins (Next Dent, Denturetect, Polident, Promolux).…”
Section: Discussionmentioning
confidence: 99%